2016
DOI: 10.1111/jtxs.12202
|View full text |Cite
|
Sign up to set email alerts
|

The Formulation Design of Elderly Special Diets

Abstract: Texture is important not only for food palatability but also for the safety of eating in recent aged society. For the elderlies, particularly those with reduced capability of eating, textural properties of food products should be modified from rheological, colloidal and tribological aspects to make the products friendly to these people. Formulation design for the texture of elderly special diets is now one of the most important tasks in Japanese food industry, and actually Japan is leading the product developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…This led to concentrations of gums that matched apparent viscosity levels of 50 cP, 135 cP, and 325 cP for IDDSI levels 1, 2, and 3 respectively when taken at 50 s −1 . Note that these levels fall within thin (1–50 cP) and nectar-thick (51–350 cP) when using the National Dysphagia Diet Task Force viscosity classification and moderately thick (50–150 cP) and extremely thick (300–500 cP) when using the Japanese Society of Dysphagia Rehabilitation scheme (National Dysphagia Diet Task Force & American Diatetic Association, 2002; Funami, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…This led to concentrations of gums that matched apparent viscosity levels of 50 cP, 135 cP, and 325 cP for IDDSI levels 1, 2, and 3 respectively when taken at 50 s −1 . Note that these levels fall within thin (1–50 cP) and nectar-thick (51–350 cP) when using the National Dysphagia Diet Task Force viscosity classification and moderately thick (50–150 cP) and extremely thick (300–500 cP) when using the Japanese Society of Dysphagia Rehabilitation scheme (National Dysphagia Diet Task Force & American Diatetic Association, 2002; Funami, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…This means that the texture of food products is important in elderly people who have dietary limitations (Nishinari, 2009) as increases in texture attributes such as hardness, chewiness, and gumminess can result in people being reluctant to eat these foods (Kohyama et al, 2002). Funami (2016) reported that digestion of food and absorption of mineral and nutrients from food is enhanced by modifications in their textural properties. Therefore, the improvement of texture is a major challenge in producing food for elderly populations, especially where they have developed various eating dysfunctions.…”
Section: Introductionmentioning
confidence: 99%
“…They tend to withdraw as much as possible from social activities and often suffer from depression and loss of the quality of life. Texture modification becomes necessary to ensure safe food consumption by elderly and dysphagia patients (Cichero, ; Funami, ; Nishinari et al, ; Smith & Wang, ). With the rapid growth of elderly populations in developed countries and even some developing countries, food industries are under a growing pressure in producing foods of appropriate texture to meet the need of elderly and dysphagia patients.…”
Section: Introductionmentioning
confidence: 99%